Preparation and properties of natural rubber/organo-montmorillonite: from lab samples to bulk material - Ivanoska-Dacikj, Aleksandra; Bogoeva-Gaceva, Gordana; Buzarovska, Aleksandra; Gjorgjiev, Igor; Raka, Luljeta (Society of Chemists and Technologists of Macedonia, 2014)
Focusing on application aspects of the rubber nanocomposites and the production and testing of industrial-sized samples, this study was performed in two phases. First, natural rubber (NR)/organo-montmorillonite (OMMT) nanocomposites containing 2–14 phr OMMT were prepared on a laboratory-sized two-roll mill. The vulcanization behavior and mechanical properties of NR/OMMT composites were compared with a referent NR compound containing 60 phr carbon black (N330) as a reinforcing filler. The x-ray diffraction (XRD) analyses showed a predominant intercalated structure for all OMMT nanocomposites. As a result, the organoclay behaved as an effective reinforcement for NR, even at loadings as low as 2 phr. This nanocomposite exhibited an improvement in tensile strength of 29% and in elongation at break of 61% in comparison with the referent NR/N330 compound. With the estimated optimal filler content, in the second phase, bulk NR/OMMT-5/steel samples were successfully produced for dynamic testing. The dynamic moduli were investigated by the method of forced vibrations. Compared to the NR/N 330 samples, NR/OMMT-5 samples showed improved hysteresis, with very low dissipating energy per cycle and significantly reduced Mullins effect.